Highly efficient mutagenesis using N-methyl-N-nitrosourea on male germ cells of maize - Tian, Huaidong; Li, Zhen; Niu, Pengfei; Tian, Chenghua; Li, Nan; Yan, Feng; Shen, Xiaohui; Ma, Hailin; Cui, Guimei (International Journal of Agricultural and Biological Engineering, 2025)
The mutagenesis with ethyl methanesulfonate (EMS) mixed in paraffin oil on maize (Zea mays L.) pollens has been the main means for inducing genic mutants of maize. However, it is necessary to develop a new technique for improving efficiency of random mutagenesis of genes in maize, and to promote mutant creation for functional-genomic research and breeding of maize. In this study, the technique of N-methyl-N-nitrosourea (MNU) mutagenesis on maize male germ cells was developed by establishing the method of MNU treatment of invitro maize pollens and screening the derived progeny populations. The phosphate-buffered protective-solution-1 (PS1) containing 30% glycerol, 15% ethylene glycol, 15% dimethyl sulfoxide, and 0.4% sucrose was determined as the optimum formula for protecting invitro pollens at 20°C; the effect of MNU concentration, treatment time, pH, and PO_4^(3-) concentration on the survival rate of pollens treated in the MNU solutions containing PS1 formula was clarified, performing the single-factor and orthogonal experiments for pollen viability; the reproductivity of treated pollens was confirmed, examining their germination and insemination; the MNU treatments under each group condition all increased the mutant-character occurrence in the M1-M2 populations derived by insemination of mutagenized male germ cells, in contrast to the EMS treatment; when the pollens were treated for 40 min in 1.0 mM MNU solution (pH: 4.8) containing 20 mM PO_4^(3-), the mutant-character incidence most-significantly reached the maximum value of 10.5%, which was 6.2 times higher than that based on the EMS treatment; the mutant population was obtained by further screening the M3 populations. The MNU-mutagenic technique remarkably improves the efficiency of broad-spectral induction of maize mutants, which can provide support for the novel functional-gene identification and diversified breeding of maize. Key words: Zea maysL.; inbred line; in vitro pollens; MNU; mutagenizationDOI: 10.25165/j.ijabe.20251806.9610Citation: Tian H D, Li Z, Niu P F, Tian C H, Li N, Yan F, et al. Highly efficient mutagenesis using N-methyl-N-nitrosourea on male germ cells of maize. Int J Agric & Biol Eng, 2025; 18(6): 48–55.